Adaptation and Validation of the Muslim Medical Students Questionnaire (MMSQ) in the Indonesian Language - Khoiriyah, Umatul; Wijaya, Diani Puspa; Musa, Ramli (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: The Muslim Medical Students Questionnaire (MMSQ) is a self-assessment tool that was designed to measure student’s Islamic competency in line with the implementation of the Islamic medical curriculum. For it to be applicable in Indonesia, this questionnaire needed to be translated and validated in the Indonesian language (Bahasa Indonesia). This study aimed to collect validity evidence of the Bahasa Indonesia version of MMSQ (BI-MMSQ). MATERIALS AND METHODS: The research process consisted of four stages: Forward and backward translation; Harmonization of the BI-MMSQ resulting from the initial stage; Pre-test of the BI-MMSQ among 30 clinical students, and finally construct validation among 225 clinical students. The completed questionnaires of 213 students were then analysed for their reliability and validity using exploratory factor analysis (EFA). RESULTS: The study showed that the scale had sufficient validity evidence; content, response process, and internal structure. The evidence of the internal structure of the tool is derived from the internal consistency (Cronbach’s Alpha is 0.85) and also from the factor analysis. Most of the items had a factor loading value of > 0.3, but it was suggested that some of those with a value of < 0.3 should be rephrased to increase their quality. The Practice domain was the most stable sub-scale since most of the items contained high factor loadings. CONCLUSION: The BI-MMSQ had sufficient validity evidence and the internal structure may be improved by alteration of a few items.